Design and experimental testing of components for the replacement of dangerous radiological sources in geological studies - Vo, Long (Kansas State University, 2020)
One of the vulnerabilities faced in modern society is the accidental or intentional dispersal of significant quantities of radionuclides into the environment. The term “dirty bomb” refers to a conventional explosive coupled with one or more radionuclides. When detonated, dirty bombs can cause immediate injuries and exposes the intended target as well as bystanders to radiation. Soon after the terrorist attacks of September 11, 2001, the United States Government commissioned a National Academy of Sciences study to consider the issues of radionuclide sources use. The study reported over 5,000 devices containing nearly 55,000 high-activity radionuclide sources are licensed as of 2008 in the United States. A significant quantity was used for medical applications (e.g. cancer therapy, sterilization, irradiation of blood) and industrial applications (e.g. gauging, well logging for exploration of oil and gas). Among the sources identified as dangerous were ¹³⁷Cs and Am-Be, primarily used in well logging applications. In 2014, the National Nuclear Security Administration awarded North Carolina State University (NCSU) a five year $25M grant to develop next generation leaders with practical experience in technical fields related to nonproliferation. The Consortium for Nonproliferation Enabling Capabilities was established. Kansas State University (KSU) is a member CNEC and was studying the replacement of dangerous radiological sources (RDRS) in well logging. RDRS prioritized the search for the replacements or alternative sources in well logging applications. Medical sources stay at fixed facilities and physical security can be enhanced to deter theft. The main objective was to produce experimental data for testing the Monte Carlo Library Least Squares (MCLLS) method. The main objective entailed the constructions of benchmarking test facilities and a prototype tool to collect radiation measurements. Experiments were designed to explore the utility of deuterium-tritium (D-T) accelerators in well logging applications. Deuterium-tritium (D-T) neutron generators have shown promising utility for oil and gas exploration. Test facilities were constructed for a ThermoFisher B322 D-T accelerator to emit neutrons within a 2500-gallon test chamber. Various materials were placed in the effectively infinite test chamber and around a tube inside the chamber. The tube acted as a borehole containing a prototype logging tool. The prototype collected neutron and gamma interactions with various samples: water, sand, limestone, saline or known mixtures of those materials. The test facilities and the prototype were used to benchmark radiation transport codes. The potential of compact accelerator neutron generators for well logging applications was explored. Pulsing capability of compact accelerators presented time as a domain for analysis. An experimentally derived parameter νΣₐ (μs^-¹) exhibited a nearly linear correlation with hydrogen index (HI) of the contents inside the test chamber. The value νΣₐ is determined by the macroscopic neutron absorption cross section of the materials inside the test chamber and the neutron speed v. The measured apparent decay time constant τₐ (μs)=1/(νΣₐ ) was found to be free of noise from borehole effects. The measured decay time constant of 2.2 MeV from hydrogen was verified by calculations of the macroscopic cross section for water, sand, and saline samples. The novel approach to derive the macroscopic neutron absorption cross section of a medium from decaying isotopes was introduced in this dissertation. Other factors such as the formation type (composition and density) and salinity (neutron absorber) were also studied. The observations and their significance warranted compact D-T accelerator as a viable alternative for radionuclide sources in well logging. The results in this study also impact non-destructive testing of bulk materials in general.
Keywords: Nuclear nonproliferation; Replacement of dangerous radiological sources; D-T accelerator neutron generator; Well logging; Hydrogen index; Oil and gas exploration